PERTUMBUHAN SAGU (Metroxylon sp) DI HUTAN ALAM PAPUA - Batseba A. Suripatty; Erny Poedjirahajoe; Satyawan Pudyatmoko; Budiadi Budiadi (JURNAL HUTAN PULAU-PULAU KECIL, 2016)
Sago plants (Metroxylon sp) is a type of palm tree that grows around swamps and waterlogged land in the tropics. Sago palms grow on muddy land, with the quantity of water varies greatly, ranging from dry land to land remained logged. The longer the land flooded, the growth of young plants (shoots / seedling) very rapidly, but the growth of the trees are very slow. This study aims to determine the relationship of the growth of sago (Metroxylon sp) with climatic factors (humidity, temperature, light) and biotic (plants or other vegetation). The results showed that the relationship of growth of sago with environmental factors, edaphic (water), climatic (humidity, light) and biotic factors (vegetation) are generally water has an influence on the growth of sago while the humidity factor for all types of places to grow, that is, the area stagnant water, temporary areas and dry areas do not affect the growth of sago.